Multi-objective optimization and assessment of recycled concrete aggregates for sustainable development: Example of the Komurhan bridge - Ulucan, Muhammed; Tas, Yavuzhan; Alyamac, Kursat Esat (Ernst & Sohn, 2023)
The main purpose of this study is to examine the advantages and disadvantages of the Komurhan bridge, built with natural aggregate concrete in Elazig, in terms of mechanical, environmental, and economic properties if certain ratios of recycled concrete aggregate (RCA) were used. For this purpose, a detailed laboratory study was designed, and concrete samples were produced, all-natural, all-recycled, and both recycled and containing natural aggregates. Different water-to-cement, aggregate-to-cement, and recycled concrete aggregate-to-total aggregate ratios were considered for the mixture designs of these samples, and the fresh and hardened concrete properties of these samples were determined. Then, statistical analyses were made using the response surface method, and numerical models were developed to predict the fresh and hardened concrete properties with high accuracy. Mixtures containing RCA, which have the same fresh and hardened concrete properties as the fresh and hardened concrete properties of the Komurhan bridge, which was selected as an example structure by using these models, were determined for optimization purposes. A detailed environmental and economic comparison of the optimization and reference mixtures was made. While making environmental assessments, energy consumption, global warming potential, waste generation, and abiotic depletion were considered. It was seen that the optimization mixtures were more economical and more environmentally friendly than the reference mixture. As a result of this study, it was predicted that the use of RCA in buildings constructed using large amounts of concrete could provide significant environmental and economic advantages and was exemplified by the Komurhan bridge.
Keywords: construction and demolition waste; earthquake; Komurhan bridge; recycled concrete aggregate; sustainable development